STRENGTHENING LOCAL AUTHORITIES THROUGH LOCAL PROCUREMENT - Shahor, Tal; Porat, Irit; Simonovich, Javier; Sharabi, Moshe (PEOPLE: International Journal of Social Sciences, 2018)
This study examines options available to local authorities to promote the local economy and create job opportunities by employing local residents, and purchasing locally made products and services, while conducting the procurement process according to proper management procedures and without detracting from the standard of the services and goods acquired.Public procurement through tenders is discussed in the context of exposing corruption and in economic terms. Usually this discussion is based on two assumptions. The first assumption maintains that a competitive process prevents corruption and bias, and the second assumption contends that the outcome will be the more efficient as it leads to selection of the most cost-effective bid according to the stipulated conditions in the published invitation to tender.This study examines whether, in its considerations, the local authority can include additional indirect benefits to the local community by preferring businesses whose public contributions exceed supply of the service or product offered in the tender. In other words, this study examines the possibility that conditions of the tender will prefer local authority residents, businesses, or employees.